2020
DOI: 10.1590/1807-1929/agriambi.v24n2p95-100
|View full text |Cite
|
Sign up to set email alerts
|

Seed physiological quality and seedling growth of pea under water and salt stress

Abstract: The aim of this study was to evaluate seed physiological quality and initial pea (Pisum sativum) seedling development at different water and salt potentials. Polyethylene glycol 6000, sodium chloride and potassium chloride solutions with different osmotic potentials (0; -0.2; -0.4; -0.6; -0.8; -1.0, and -1.2 MPa) were used, and the experiment had a 3 × 7 factorial arrangement. The physiological quality and initial seedling growth characteristics (first germination count, final germination count, strong normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 12 publications
4
29
0
Order By: Relevance
“…Those two cultivars also showed the greatest decrease in germination percentage at -4 bar of drought stress. Drought stress caused by PEG negatively affected germination on pea genotypes in the studies of Okçu et al (2005) and Pereira et al (2020). Similar results have also been obtained for lentil genotypes (Muscolo et al 2013), grass pea varieties (Aslan and Atış, 2018), and some alfalfa genotypes (Özkurt et al, 2018).…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Those two cultivars also showed the greatest decrease in germination percentage at -4 bar of drought stress. Drought stress caused by PEG negatively affected germination on pea genotypes in the studies of Okçu et al (2005) and Pereira et al (2020). Similar results have also been obtained for lentil genotypes (Muscolo et al 2013), grass pea varieties (Aslan and Atış, 2018), and some alfalfa genotypes (Özkurt et al, 2018).…”
Section: Resultssupporting
confidence: 61%
“…Although the reduction rates of cultivars at -4 bar of drought stress were similar, as with the reduction rates of seedling length, the Töre, Özkaynak, and Ürünlü cultivars had low reduction rates, whereas the Taşkent, Ulubatlı, and Gölyazı cultivars had high ones. Okçu et al (2005), Petrović et al (2016), andPereira et al (2020) all observed a remarkable decrease in the fresh and dry weights of pea seedlings due to the decreased availability of water as doses of NaCl and PEG increased.…”
Section: Resultsmentioning
confidence: 98%
“…Negative values of osmotic potential delay and reduce the speed and percentage of germination after impairing the sequence of germination events during water absorption (Pereira;Caixeta, 2020). When water is removed below the limit tolerated by the cell, due to drought or a saline environment, the concentration of solutes may increase.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that simulate water and saline stress in the soil have been performed under laboratory conditions using aqueous solutions of different osmotic potentials to moisten the germination substrates (Pereira;Caixeta, 2020). Such stress factors usually reduce the speed and percentage of seed germination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation